Alexander Hamilton [compact disc, abridged] - Chernow, Ron (Penguin Audio, 2016)
Pulitzer Prize winning author Ron Chernow presents a landmark biography of Alexander Hamilton, the Founding Father who galvanized, inspired, scandalized, and shaped the newborn nation.